ROLE OF DOPPLER SONYM OF MYSTERIOLOGY IN ASSESSMENT LEFT VENTRICULAR SYSTOLIC FUNCTION IN PATIENTS HEART FAULT (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the role of doppler ultrasound in the assessment of left ventricular functionin patients with heart failure before and after pacemaker implantation.Subjects and research methods: A descriptive cross-sectional study was performed on 33 patientswith severe heart failure treated at Bach Mai Hospital from 2008 to 2015.Results: The results showed that there was a statistically significant difference in the muscle fibershortening index D (%) ) after implantation was 4.5% higher than the value measured at the time ofadmission (t0). Ejection fraction EF (Teich) at post-treatment was 4.8% and 7.1% higher, respectively,than EF at hospital admission. The EF ejection fraction (Biplane) decreased significantly (5.3%vs 7.6%). The results of left atrial ultrasound showed that the mean left atrial volume at the timeof treatment was reduced by 4.4 ml/m2 compared to the mean left atrial volume at the time ofadmission. This difference is statistically significant with p < 0.05. Most of the echocardiographicindices decreased significantly after treatment.
Keywords: Doppler ultrasound, left ventricle, heart failure.